Tax arbitrage and labor supply - Agell, Jonas 1957-; Persson, Mats (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1998)
We examine how tax avoidance in the form of trade in well-functioning asset markets affects the basic labor supply model. We argue that models that integrate tax arbitrage and labor supply decisions may shed light on a number of positive and normative questions concerning modern systems of income taxation. Such models also appear to have strong implications for empirical research. Studies that ignore the effects of tax arbitrage and asset trade on labor supply incentives may easily come up with biased estimates of the tax responsiveness of the hours supply of high-wage individuals. Finally, because of tax avoidance in the form of asset trade, international comparisons of income inequality will exaggerate the redistributive achievements of high-tax countries like Sweden.